Каждый день как последний: [роман] / Ольга Володарская - Володарская Ольга (Нет запретных тем, 2014)
Экземпляры: ф.1 (20141114) / Инвентарный номер: 51127 / Цена: 190. 00. / Сис.шифр: Р2 / Авт.знак: В 68 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4